Soviet robots in the solar system mission technologies and discoveries - Huntress, JR., Wesley T. (Wesley Theodore) (Springer praxis books, 2011)
The Soviet robotic space exploration program began in a spirit of bold adventure and technical genius. It ended after the fall of the Soviet Union and the failure of its last mission to Mars in 1996. Soviet Robots in the Solar System chronicles the scientific and engineering accomplishments of this enterprise from its infancy to its demise. Each flight campaign is set into context of national politics and international competition with the United States. Together with its many detailed illustrations and images, Soviet Robots in the Solar System presents the most detailed technical description of Soviet robotic space flights provides a unique insight into programmatic, engineering, and scientific issues covers mission objectives, spacecraft engineering, flight details, scientific payload and results describes in technical depth Soviet lunar and planetary probes.